Tradisi Kenduri Turun Kapal Di Desa Temiang Kecamatan Bandar Laksamana - Husaini, Husaini; Fahrezi, Muhammad; Abdulrahman, Abdulrahman (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The tradition of kenduri getting off the boat is an ancestral tradition of the fishing community in Temiang Village, Bandar Laksmana District. The purpose of this study is to explain how the belief and what influences the community to maintain it carry out the Kenduri Get off the Ship tradition to fishermen in Temiang Village, Bandar Laksmana District. As for this research using qualitative methods and descriptive approach. The results of this study indicate that there are still fishing communities in Temiang Village who practice the Kenduri Get off the Ship tradition. Those who believe in and practice the tradition of celebrating Turu Kapali are influenced by history or tragic stories from the past and the advice of the elders. on the banks of the river or in front of the house, and this tradition involves the whole community wanting to help lower the boat into the river, preparations for this tradition include preparing food and prayers which will be carried out with religious and community leaders